Le Buddha comme épicentre sismique et comme sismologue - Eltschinger, Vincent (Revue de l'histoire des religions, 2024)
Abundant as they may be in the literary sources of Indian Buddhism, earthquakes are hardly reducible to "catastrophic" events of a purely natural and historical character. Rather, they have to be read against a "hiero-historical" background as signs celebrating the main events in the biography of a (future) Buddha, manifesting the superior psychic powers of certain beings (monks/nuns, deities), or marking the approval of the (goddess) Earth. The salvific intention behind them explains why they are perceived, if not always as pleasant, at least as not causing casualties or damage in spite of their at times terrifying nature. This interpretation, though largely dominant, coexists with various astrological and seismo-mantic uses of earthquakes.